Pneumonia, gastrointestinal symptoms, comorbidities, and coinfections as factors related to a lengthier hospital stay in children with COVID-19—analysis of a paediatric part of Polish register SARSTer. Issue 3 (4th March 2022) - Mania, Anna; Pokorska-Śpiewak, Maria; Figlerowicz, Magdalena; Pawłowska, Małgorzata; Mazur-Melewska, Katarzyna; Faltin, Kamil; Talarek, Ewa; Zawadka, Konrad; Dobrzeniecka, Anna; Ciechanowski, Przemysław; Łasecka-Zadrożna, Joanna; Rudnicki, Józef; et al.
Abstract: Background: Although COVID-19 is associated with a mild course in children, a certain proportion requires admission to hospital due to SARS-CoV-2 infection and coexisting diseases. The prospective multicenter study aimed to analyze clinical factors influencing the length of the hospital stay (LoHS) in children with COVID-19. Methods: The study included 1283 children from 14 paediatric infectious diseases departments with diagnosed SARS-CoV-2 infection. Children were assessed in respective centres regarding indications for admission to hospital and clinical condition. History data, clinical findings, laboratory parameters, treatment, and outcome, were collected in the paediatric SARSTer register. The group of children with a hospital stays longer than seven days was compared to the remaining patients. Parameters with a statistically significant difference were included in further logistic regression analysis. Results: One thousand one hundred and ten children were admitted to the hospital, 763 children were hospitalized >24 h and 173 children >7 days. 268 children had comorbidities. Two hundred and eleven children had an additional diagnosis with coinfections present in 135 children (11%). Factors increasing the risk of higher LoHS included pneumonia [odds ratio—OR 3.028; 95% confidence interval—CI (1.878–4.884)], gastrointestinal symptoms [OR = 1.556; 95%CI (1.049–2.322)], or rash [OR = 2.318; 95%CI (1.216–4.418)] in initial clinical findings. Comorbidities [OR = 2.433; 95%CI (1.662–3.563)], an additional diagnosis [OR = 2.594; 95%CI (1.679–4.007)] and the necessity of the empirical antibiotic treatment [OR = 2.834; 95%CI (2.834–6.713)] were further factors related to higher LoHS. Conclusions: The clinical course of COVID-19 was mild to moderate in most children. Factors increasing the risk of higher LoHS included pneumonia, gastrointestinal symptoms, comorbidities, an additional diagnosis, and the empirical antibiotic treatment.